Teacher professionalism in digital era - Sugiyanto Sugiyanto; Nur Ahyani; Nila Kesumawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Technological developments make changes in life. Students are in a digital environment full of information. Countries change educational goals. Many educational innovations have also been carried out to support this. The hope of educational innovation is the support and integration of information and communication technology (ICT) in the learning process. So that there is an increase in the quality of student learning. Students today must have communication, collaboration, critical thinking and creative and innovative skills. These skills must be included in the learning process in class. To support this, all teacher competencies must be improved, especially professional competences. This research uses literature study. The purpose of this study is to reveal how the professionalism of teachers in the 4.0 revolution era in improving the quality of education.